Cytotoxic Activity of Salvia Officinalis Extract Mediated by the Inhibition of JAK2 in Breast Cancer - Alawadi Dawood, Salma (AUC Knowledge Fountain, 2023)
Background: Breast cancer is the most common type of invasive cancer in women in their forties and fifties. Recent evidence suggests that JAK2/STAT3 signaling is constitutively active in breast cancer. Previous studies suggest that plant extracts, including Salvia Officinalis, have strong cytotoxic effects on breast cancer cells. The differential expression of miRNAs is also strongly linked to cancer development. Aim: In the current study, we hypothesize that S. Officinalis extract suppresses JAK2 expression and has strong anticancer potential in MCF7 breast cancer cell lines. Methods: GC-MS analysis showed the presence of flavonoids in dried leaf of Salvia officinalis Extract. The cytotoxicity of S. Officinalis was compared to Cisplatin on human breast (MCF-7) cells. Bioinformatic analysis was performed to detect the link between JAK2 and different microRNAs. qPCR assessment of microRNAs and JAK2 , BAX, Bcl-xL and BIRC5 mRNAs was performed. miR-216a-5p was overexpressed in MCF7 cells to test its anticancer potential. Results: GC-MS analysis showed the presence of anticancer and antioxidant compounds (Linolein and Apigenin). S. Officinalis extract reduced cell proliferation of MCF-7 cells with an IC50 range from 5.123 to 6.345 mg/mL (pS. Officinalis was also safe for the human skin fibroblast, suggesting that S. Officinalis has anticancer activity and is less harmful to normal cells (p S. Officinalis displayed morphological changes consistent with apoptosis. Bioinformatic analysis revealed that JAK2 contains theoretical binding sites of miR-101, miR-216, and miR-204 in its 3` UTR. qPCR revealed that three miRs (miR-101-5p, miR-216a-5p & miR-204-5p) were less expressed in breast cancer cell lines than in normal cell lines (P=0.0022). S. Officinalis and cisplatin reduced the expression of miR-101-5p (pS. Officinalis reduced the expression of miR-216a-5p (pAlso, qPCR showed that S. Officinalis and miR-216a-5p mimics significantly reduced JAK2 mRNA expression (p<0.0001). S. Officinalis and overexpression of miR-216a-5p both increased BAX expression while decreasing Bcl-xL and BIRC5 expression.Conclusions: S. Officinalis has significant anticancer potential mediated through the increased mRNA expression of BAX and reduced expression of JAK2, Bcl-xL, and BIRC5 mRNAs. As well as the reduced expression of miR-101-5p & miR-216a-5p. Although the overexpression of miR-216a-5p in MCF7 increased BAX expression and significantly decreased JAK2, BIRC5, and Bcl-xL expression, it did not lead to cell death in vitro.